Resin composition, resin film, article and separation method
By introducing an acrylate polymer with an ethylene carbonate structure into the adhesive and releasing carbon dioxide with a catalyst, the problem of large or deep product decomposition is solved, and an environmentally friendly and easy-to-separate decomposition effect is achieved.
Patent Information
- Application Number
- JP2023123095
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, when dealing with large products or deep products, water-soluble adhesives are difficult to effectively decompose, and the existing thermally expanded microsphere particle size cannot meet the application needs of thin layers. At the same time, the use of environmentally unfriendly gas materials increases environmental protection pressure.
Acrylate polymer containing an ethylene carbonate structure is used to decompose the ethylene carbonate structure through the nucleophilic attack of the catalyst to release carbon dioxide, reduce the adhesion force and facilitate separation, and control the particle size within the range of 10nm-1μm. Nucleophilic ion generators such as tetrabutylammonium bromide are used as catalysts.
It achieves convenient decomposition of large or deep products, and has the effect of separation with suitable particle size, and uses carbon dioxide to decompose to reduce adhesion, which meets environmental protection requirements.
Smart Images

Figure 2025019470000014 
Figure 2025019470000001 
Figure 2025019470000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, a resin film formed from the resin composition, an article including the resin film, and a method for separating members constituting the article. [Background technology]
[0002] In recent years, from the perspective of environmental consideration, there has been a demand for electronic devices, electrical appliances, etc. that can be easily dismantled when they are no longer needed (easy dismantling). The parts that are generated through dismantling can be recycled or reused.
[0003] For example, when components constituting a product are attached to each other with an adhesive sheet, the adhesiveness of the adhesive sheet is reduced by an external stimulus to facilitate separation and peeling of the components. As an example of such an adhesive sheet, Patent Document 1 discloses an adhesive sheet made of a water-soluble adhesive that can be disassembled and peeled by immersing in water. Patent Document 2 discloses a heat-foamable removable adhesive tape that maintains high normal adhesive strength when bonded, but reduces adhesive strength by heating when separating and dismantling the bonded parts, allowing easy separation and dismantling. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2023-35332 A [Patent Document 2] JP 2014-214208 A Summary of the Invention [Problem to be solved by the invention]
[0005] When dismantling a product using the adhesive sheet disclosed in Patent Document 1, at least the adhesive sheet portion needs to be brought into contact with water; however, if the product is large or if the adhesive sheet is located deep inside the product and it is difficult for water to reach it, handling becomes difficult.
[0006] Furthermore, easy dismantling is sometimes required even for products that do not use adhesive sheets, and in such cases, the adhesive sheet disclosed in Patent Document 1 cannot adequately meet the requirements.
[0007] The average particle size of the thermal blowing agent (particularly the thermally expandable microspheres) disclosed in Patent Document 2 is generally about 1 to 80 μm from the standpoint of dispersibility, thin layer formability, etc., which cannot be adequately used depending on the application of the pressure-sensitive adhesive sheet.
[0008] Furthermore, in recent years, interest in emulsion-type resin compositions and chemical products using gases such as carbon dioxide, which are considered to be a cause of global warming, as raw materials has been increasing due to legal regulations and environmental considerations, etc. Therefore, further options that are environmentally friendly and enable easier dismantling for easier handling are required.
[0009] The present invention has been made in consideration of the above circumstances, and has an object to provide a new means for achieving easy disassembly. [Means for solving the problem]
[0010] In order to achieve the above object, first, the present invention provides a polymer comprising a monomer unit represented by the following formula (1): [ka] or a resin composition comprising fine particles containing the (meth)acrylic ester polymer and a catalyst capable of nucleophilically attacking a carbon atom constituting a carbonyl group in the ethylene carbonate structure, thereby decomposing the ethylene carbonate structure and releasing carbon dioxide (Invention 1).
[0011] In the resin composition according to the above invention (Invention 1), the ethylene carbonate structure present in the (meth)acrylic acid ester polymer is decomposed by heat treatment under the action of the above catalyst, and carbon dioxide is released. Therefore, even if a resin film (adhesive layer, etc.) formed from the above resin composition is in close contact with another object, the carbon dioxide accumulates at the interface between the resin film and the object, thereby reducing the adhesion. As a result, it becomes possible to easily separate the resin film from the object.
[0012] In the above invention (Invention 1), it is preferable that the particle size (D50) of the dispersoid is 10 nm or more and 1 μm or less, and the average particle size of the fine particles is 10 nm or more and 1 μm or less (Invention 2).
[0013] In the above inventions (Inventions 1 and 2), the (meth)acrylic acid ester polymer preferably contains, as a monomer unit constituting the polymer, the ethylene carbonate-containing monomer in an amount of 10% by mass or more and 99.9% by mass or less (Invention 3).
[0014] In the above inventions (Inventions 1 to 3), the ethylene carbonate-containing acrylic monomer is preferably a compound represented by the following formula (2) or (3) (Invention 4). [ka] (In the formula, n represents an integer of 0 or more.) [ka] (In the formula, n represents an integer of 0 or more.)
[0015] In the above inventions (Inventions 1 to 4), the catalyst is a nucleophilic anion generator capable of generating a nucleophilic anion, and the nucleophilic anion is a fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ) and hydroxide ion (OH - ) is preferably at least one of the above (Invention 5).
[0016] In the above inventions (Inventions 1 to 5), the catalyst is preferably at least one of tetrabutylammonium bromide and tetra-N-butylammonium fluoride (Invention 6).
[0017] In the above inventions (Inventions 1 to 6), the (meth)acrylic acid ester polymer preferably contains acrylic acid as a monomer unit constituting the polymer (Invention 7).
[0018] In the above inventions (Inventions 1 to 7), the (meth)acrylic acid ester polymer is preferably obtained by emulsion polymerization of monomer units containing the ethylene carbonate-containing acrylic monomer (Invention 8).
[0019] In the above inventions (Inventions 1 to 8), the microparticles are preferably obtained by emulsion polymerizing monomer units containing the ethylene carbonate-containing acrylic monomer to produce an emulsion containing the (meth)acrylic acid ester polymer as a dispersoid, and then removing the dispersion medium constituting the emulsion, and pulverizing the resulting residue (Invention 9).
[0020] Secondly, the present invention provides a resin film (Invention 10) characterized by being formed from the above-mentioned resin composition (Inventions 1 to 9).
[0021] Thirdly, the present invention provides an article comprising the above-mentioned resin film (Invention 11) and a member provided on at least one surface of the resin film (Invention 11).
[0022] A fourth invention provides a separation method for separating the resin film and the member in the article (Invention 11), comprising the steps of: heating the resin film to decompose the ethylene carbonate structure and generate carbon dioxide gas; and separating the resin film and the member by the carbon dioxide gas accumulated at the interface between the resin film and the member (Invention 12). Effect of the Invention
[0023] The resin composition according to the present invention provides a new means for achieving easy dismantling. [Brief description of the drawings]
[0024] [Figure 1] FIG. 11 is a diagram showing the state of foaming after heating and the state of peeling off for a dismantling ease confirmation sample according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, an embodiment of the present invention will be described. [Resin composition] The resin composition according to the present embodiment contains, as a monomer unit constituting a polymer, a monomer represented by the following formula (1): [ka] or fine particles containing the (meth)acrylic acid ester polymer as a dispersoid, and a catalyst capable of carrying out a nucleophilic attack on a carbon atom constituting a carbonyl group in the ethylene carbonate structure, thereby decomposing the ethylene carbonate structure and releasing carbon dioxide.
[0026] In the resin composition according to the present embodiment, the ethylene carbonate structure can be decomposed by the action of the catalyst to release carbon dioxide. By using a resin composition having such properties, it is possible to manufacture a product with excellent ease of dismantling. That is, the carbon dioxide released as described above can be used to reduce the adhesion between the members constituting the product, and as a result, the product can be easily dismantled. For example, when members are bonded together by a pressure-sensitive adhesive sheet manufactured using the resin composition according to the present embodiment as a material, the above-mentioned ethylene carbonate structure is decomposed to generate carbon dioxide, which is stored at the interface between the pressure-sensitive adhesive sheet and the member, and the pressure-sensitive adhesive sheet and the member can be physically separated.
[0027] As the above-mentioned catalyst, for example, a nucleophilic anion generator capable of generating nucleophilic anions by a predetermined stimulus is suitable. The nucleophilic anion performs a nucleophilic attack on the carbon atom constituting the carbonyl group in the ethylene carbonate structure, thereby enabling efficient decomposition of the ethylene carbonate structure. When a nucleophilic anion generator that generates nucleophilic anions by heating is used as the above-mentioned nucleophilic anion generator, it becomes possible to dismantle a product using the resin composition according to the present embodiment by heating as an external stimulus.
[0028] 1. Emulsions and microparticles The emulsion in this embodiment is not particularly limited as long as it contains the above-mentioned (meth)acrylic acid ester polymer as a dispersoid. The fine particles in this embodiment are not particularly limited as long as they contain the above-mentioned (meth)acrylic acid ester polymer.
[0029] However, the emulsion in this embodiment is preferably an emulsion containing, as a dispersoid, a (meth)acrylic acid ester polymer obtained by emulsion polymerization of a monomer unit containing the above-mentioned ethylene carbonate-containing acrylic monomer. Furthermore, the fine particles in this embodiment are preferably fine particles obtained by removing the dispersion medium constituting the emulsion and pulverizing the residue obtained.
[0030] The (meth)acrylic acid ester copolymer is not particularly limited so long as it contains, as a monomer unit constituting the polymer, an ethylene carbonate-containing acrylic monomer having an ethylene carbonate structure represented by the above formula (1).
[0031] The ethylene carbonate-containing acrylic monomer is not particularly limited as long as it contains an ethylene carbonate structure and has a (meth)acryloyl group (structure). A preferred example of the ethylene carbonate-containing acrylic monomer is a (meth)acrylic acid ester having a structure in which an organic group having an ethylene carbonate structure is bonded to a (meth)acryloyloxy group. An example of such a (meth)acrylic acid ester is represented by the following formula (2): [ka] or an acrylic acid ester represented by the following formula (3): [ka] or a methacrylic acid ester represented by the following formula (4): [ka] In any of the formulas (2) to (4), n and m are integers of 0 or more, and X is hydrogen or a methyl group.
[0032] Among the (meth)acrylic acid esters represented by the above formulas (2) to (4), from the viewpoint of easy release of carbon dioxide gas, (meth)acrylic acid esters in which n and m are each 1 or more are preferred, and (meth)acrylic acid esters in which n and m are each 2 or more are preferred. The upper limit of each of the above n and m is not particularly limited, but from the viewpoint of polymerizability, it is preferably 10 or less, more preferably 6 or less, particularly preferably 4 or less, and even more preferably 3 or less. Among these, (meth)acrylic acid esters in which n=1 in the above formulas (2) and (3) are preferred, and (2-oxo-1,3-dioxolan-4-yl)methyl methacrylate in which n=1 in the formula (3) is particularly preferred. The ethylene carbonate-containing monomer may be used alone or in combination of two or more.
[0033] As disclosed in JP 2006-335971 A, the ethylene carbonate-containing monomer can be produced by adding CO2 to the epoxy group of a (meth)acrylate having an epoxy group to introduce a carbonate group. That is, the (meth)acrylic acid ester copolymer according to the present embodiment using the ethylene carbonate-containing monomer can be produced using carbon dioxide as a production raw material, and therefore carbon dioxide can be effectively utilized.
[0034] The (meth)acrylic acid ester copolymer in this embodiment preferably contains 1% by mass or more of ethylene carbonate-containing acrylic monomer, particularly preferably contains 5% by mass or more, and more preferably contains 10% by mass or more. This makes it easier for the resin film formed from the resin composition according to this embodiment to generate carbon dioxide well. In addition, the (meth)acrylic acid ester copolymer in this embodiment preferably contains 99.9% by mass or less of ethylene carbonate-containing acrylic monomer, particularly preferably contains 99.5% by mass or less, and more preferably contains 99.0% by mass or less. This makes the (meth)acrylic acid ester copolymer contain sufficient other constituent monomers, and the (meth)acrylic acid ester copolymer is more likely to have the desired performance.
[0035] The (meth)acrylic acid ester copolymer in this embodiment may contain a monomer other than the above-mentioned ethylene carbonate-containing acrylic monomer as a monomer unit constituting the polymer. For example, examples of the monomer include (meth)acrylic acid alkyl esters having an alkyl group with 1 to 12 carbon atoms; monomers containing reactive functional groups such as hydroxyl groups, carboxyl groups, and amino groups; (meth)acrylic acid esters containing alkoxyalkyl groups; (meth)acrylic acid esters having aromatic rings such as phenyl (meth)acrylate; non-crosslinkable acrylamides such as acrylamide and methacrylamide; (meth)acrylic acid esters having non-crosslinkable tertiary amino groups such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; and styrene. These may be used alone or in combination of two or more.
[0036] Among the above, the (meth)acrylic acid ester copolymer in the present embodiment preferably contains acrylic acid, which corresponds to a monomer containing a carboxy group, as a monomer unit constituting the polymer. By containing acrylic acid in the (meth)acrylic acid ester copolymer, it becomes easy to adjust the particle size (D50) of the obtained emulsion or the average particle size of the fine particles.
[0037] In the present embodiment, when the (meth)acrylic acid ester copolymer contains acrylic acid as a monomer unit constituting the polymer, the content is preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and more preferably 0.5% by mass or more. The content is preferably 99% by mass or less, particularly preferably 98% by mass or less, and more preferably 97% by mass or less. This makes it easy to adjust the particle size (D50) of the resulting emulsion or the average particle size of the fine particles while ensuring a sufficient amount of the above-mentioned ethylene carbonate structure in the (meth)acrylic acid ester copolymer.
[0038] As described above, the (meth)acrylic acid ester polymer in this embodiment is preferably obtained by emulsion polymerization of monomer units containing an ethylene carbonate-containing acrylic monomer. A conventionally known method can be used as the emulsion polymerization method. For example, the ethylene carbonate-containing acrylic monomer, the other monomers described above as desired, and an emulsifier are stirred in water as a dispersion medium, and then a polymerization initiator is added thereto and stirred at a predetermined temperature to allow emulsion polymerization to proceed.
[0039] The emulsifier is not particularly limited, but from the viewpoint of improving dispersion stability, anionic emulsifiers or nonionic emulsifiers are preferred, and anionic emulsifiers are more preferred.
[0040] Examples of anionic emulsifiers include sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, polyoxyethylene polycyclic phenyl ether sulfate, sodium polyoxyethylene alkyl ether sulfate, and allyl alkyl sulfosuccinate. Examples of nonionic emulsifiers include polyoxyethylene alkyl ether and polyoxyethylene alkyl phenyl ether. Among these, polyoxyethylene polycyclic phenyl ether sulfate is particularly preferred. These emulsifiers may be used alone or in combination of two or more.
[0041] From the viewpoint of the stability of the emulsion polymerization reaction and the viewpoint of preventing the deterioration of physical properties due to the remaining unreacted emulsifier, the content of the emulsifier is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, relative to 100 mass of the total amount of all monomers. The content of the emulsifier is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 mass of the total amount of all monomers.
[0042] The polymerization initiator may be either water-soluble or oil-soluble, and examples thereof include azo compounds such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride and 2,2'-azobis(2-amidinopropane) dihydrochloride, persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate, and peroxides such as benzoyl peroxide, t-butyl hydroperoxide, and hydrogen peroxide. Redox initiators such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peracid and sodium ascorbate may also be used. The polymerization initiator may be used alone or in combination of two or more. Among these, ammonium persulfate is preferred from the viewpoint of excellent polymerization stability. These polymerization initiators may be used alone or in combination of two or more.
[0043] From the viewpoint of accelerating the polymerization rate, the content of the polymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the total amount of all monomers. The content of the polymerization initiator is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the total amount of all monomers.
[0044] The temperature and stirring conditions after the addition of the polymerization initiator may be any conditions that allow the dispersoid to be sufficiently dispersed, and for example, the temperature is preferably 60 to 90° C., particularly preferably 65 to 85° C., and more preferably 70 to 80° C. The stirring conditions are preferably 50 to 200 rpm, particularly preferably 70 to 180 rpm, and more preferably 100 to 150 rpm. The stirring time is preferably 10 to 180 minutes, particularly preferably 10 to 60 minutes, and more preferably 10 to 30 minutes.
[0045] Furthermore, it is preferable to further add an aqueous alkali solution such as aqueous ammonia, various water-soluble amines, an aqueous sodium hydroxide solution, or an aqueous potassium hydroxide solution to the emulsion obtained by emulsion polymerization to adjust the pH to 5 to 9, and particularly to 6 to 8.5. This makes it possible to improve the stability of the dispersion.
[0046] The solid content concentration of the obtained emulsion is preferably from 10 to 80% by mass, more preferably from 25 to 70% by mass, and further preferably from 45 to 65% by mass.
[0047] In the obtained emulsion, the particle size (D50) of the dispersoid composed of the (meth)acrylic acid ester copolymer is preferably 10 nm or more, more preferably 30 nm or more, particularly preferably 50 nm or more, and even more preferably 100 nm or more. The particle size (D50) is preferably 1 μm or less, particularly preferably 0.8 μm or less, and even more preferably 0.6 μm or less. By having the above-mentioned particle size (D50) of the dispersoid in the above range, the resin film formed from the resin composition according to this embodiment has more thickness options, is easily capable of releasing sufficient carbon dioxide, and can be applied to a wide range of applications of easy dismantling. Details of the measurement method of the particle size (D50) are as described in the examples described later.
[0048] The method for removing the dispersion medium from the emulsion obtained as described above is not particularly limited, and for example, the emulsion is left to stand under a predetermined temperature environment to dry the dispersion medium. In this case, the temperature is preferably 25°C or higher, particularly preferably 40°C or higher, and more preferably 45°C or higher. The temperature is preferably 100°C or lower, particularly preferably 90°C or lower, and more preferably 80°C or lower. Furthermore, the drying time is preferably 1 hour or more, particularly preferably 2 hours or more, and more preferably 3 hours or more. The time is preferably 72 hours or less, particularly preferably 48 hours or less, and more preferably 24 hours or less. As a method for removing the dispersion medium from the emulsion obtained as described above, filtration, centrifugation, etc. may be performed. In addition, the fine particles may be washed with water or various organic solvents for the purpose of removing the surfactant remaining on the surface of the fine particles.
[0049] As described above, by removing the dispersion medium from the emulsion, the dispersoid remains as a residue. The method of pulverizing this residue to obtain fine particles is not particularly limited, and can be appropriately selected depending on the state of aggregation, and examples of such methods include dry pulverization methods such as mortar pulverization, hammer mills, jot mills, and bead mills.
[0050] The average particle size of the fine particles obtained as described above is preferably 10 nm or more, more preferably 20 nm or more, particularly preferably 30 nm or more, and even more preferably 100 nm or more. When the average particle size is 10 nm or more, the resin film formed from the resin composition according to this embodiment is likely to release sufficient carbon dioxide. In addition, the average particle size is preferably 1 μm or less, particularly preferably 0.9 μm or more, and even more preferably 0.8 μm or less. When the average particle size is within the above range, the fine particles are easily mixed and dispersed in the resin composition according to this embodiment. The average particle size of the fine particles is measured by observation using a scanning electron microscope, and the details are as described in the examples described later.
[0051] 2. Catalyst The catalyst in the present embodiment is not particularly limited as long as it is capable of performing a nucleophilic attack on the carbon atom constituting the carbonyl group in the ethylene carbonate structure, thereby decomposing the ethylene carbonate structure and releasing carbon dioxide. Preferred examples of the catalyst include nucleophilic anion generators capable of generating nucleophilic anions, and in particular, nucleophilic anion generators capable of generating nucleophilic anions in response to a predetermined external stimulus.
[0052] Examples of the nucleophilic anion include fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ), hydroxide ion (OH - ) and the like, and among these, fluoride ions (F - ) and bromide ion (Br - ) is preferred, and fluoride ion (F -Examples of the cation constituting the nucleophilic anion generator include a quaternary ammonium cation, an imidazolium cation, a pyrrolidinium cation, a pyridinium cation, a piperidinium cation, a phosphonium cation, an alkali metal ion, an alkaline earth metal ion, and the like, and among these, a quaternary ammonium cation is preferred.
[0053] Specific preferred examples of the nucleophilic anion generator include tetrabutylammonium fluoride (TBAF), tetrabutylammonium bromide (TBAB), 1-ethyl-3-methylimidazolium bromide, tetrabutylphosphonium bromide, sodium hydroxide, etc., and among these, tetrabutylammonium fluoride (TBAF) and tetrabutylammonium bromide (TBAB) are preferred. These nucleophilic anion generators may be used alone or in combination of two or more.
[0054] The above-mentioned external stimulus may be heating, irradiation with active energy rays (laser irradiation, microwave irradiation, ultraviolet irradiation, etc.), etc., among which heating is preferred. Heating is easy to treat, and is preferred because it is easier to deliver the stimulus to the resin film formed from the resin composition according to the present embodiment even when the resin film is deep inside the product, compared to other cases.
[0055] The content of the catalyst in the resin composition according to the present embodiment is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the emulsion or fine particles. The content of the catalyst is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the emulsion or fine particles. The content of the catalyst within the above range makes it easier to generate carbon dioxide efficiently.
[0056] 3. Other Ingredients The resin composition according to the present embodiment may contain components other than the emulsion, fine particles, and catalyst described above. In particular, such other components can be appropriately selected according to the type of resin film formed from the resin composition according to the present embodiment.
[0057] For example, when forming a pressure-sensitive adhesive layer as a resin film, the resin composition preferably contains a pressure-sensitive adhesive component as a main material, such as an acrylic pressure-sensitive adhesive (acrylic polymer), etc. Also, when forming a surface coating layer as a resin film, the resin composition preferably contains a curable component, etc. as a main material.
[0058] 4. Method for preparing resin composition The method for preparing the resin composition according to this embodiment is not particularly limited, and for example, the resin composition can be obtained by mixing the above-mentioned emulsion or fine particles, a catalyst, and other components, if desired, in a solvent.
[0059] [Resin film / article] Another embodiment of the present invention relates to a resin film formed from the above-mentioned resin composition and an article including the resin film.
[0060] The resin film according to the present embodiment is not particularly limited as long as it is formed from the resin composition according to the present embodiment. Specific examples of the resin film include a pressure-sensitive adhesive layer, an adhesive layer, a self-supporting film, and a surface coat layer and an anchor coat layer formed on the surface of a specific substrate. In this specification, the term "self-supporting film" refers to a film that has a strength that allows it to be handled alone without being damaged even without a support, and can maintain its film shape.
[0061] For example, when the resin film according to the present embodiment is an adhesive layer, it may be in the form of an adhesive sheet having a resin film on at least one side of a substrate (film, paper, etc.), or an adhesive sheet having a release material on both sides of the resin film. When the resin film is a surface coating layer, it may be, for example, a coated film having a substrate (film, paper, etc.) and a surface coating layer provided on the substrate. When the resin film is a self-supporting film, the article may be an adhesive sheet or hard coat film having the self-supporting film, or may be a substrate film consisting of only the self-supporting film.
[0062] In addition, the article according to the present embodiment preferably includes the resin film and a member provided on at least one surface of the resin film. The resin film releases carbon dioxide when heated as an external stimulus, so that the member and the resin film can be dismantled. The material of the member is not particularly limited. Examples include polyolefins such as polyethylene, polypropylene, polybutene, and polystyrene; engineering plastics such as polycarbonate, polyester, polyamide, and polyacetal; metal, glass, and rubber. Examples of applications of such articles are not particularly limited, and the article can be used for applications such as automobiles and vehicles (bullet trains and trains), electrical products, building materials, woodworking, and bookbinding and packaging. Examples of applications related to automobiles include adhesion of interior materials such as ceilings, doors, and seats, adhesion and sealing of exterior materials such as automobile lighting fixtures such as lamps, and side moldings. Specifically, the article can be suitably used to bond and seal a plastic housing that holds a light source and a lens that protects the light source when manufacturing automobile lighting fixtures. Examples of electrical applications include assembly of lamp shades, speakers, and the like. Further applications in the field of building materials and woodworking include adhesion of doors, access floors, laminate floors, furniture assembly, edge bonding, profile wrapping, etc. in construction sites and factory manufacturing of building materials.
[0063] Furthermore, another embodiment of the present invention relates to a separation method for separating components constituting the article according to the present embodiment, and in particular, to a separation method for separating the resin film and the components in the article.
[0064] The separation method preferably includes a step of heating the resin film to decompose the ethylene carbonate structure and generate carbon dioxide gas (gas generation step), and a step of separating the resin film and the member by the carbon dioxide gas accumulated at the interface between the resin film and the member (separation step).
[0065] The heating conditions in the gas generation step can be appropriately set depending on the form of the article, but for example, the temperature is preferably 150° C. to 250° C., particularly preferably 160° C. to 230° C., and more preferably 170° C. to 200° C. The heating time is preferably 1 minute to 30 minutes, particularly preferably 2 minutes to 15 minutes, and more preferably 3 minutes to 10 minutes.
[0066] The heating means is not particularly limited, and examples thereof include a method of heating in an oven, a method of heating with a heat gun, a method of heating with a hot plate, and the like.
[0067] After the heating, the article is preferably left to stand until a sufficient amount of carbon dioxide gas is accumulated at the interface between the resin film and the member. After a sufficient amount of carbon dioxide gas has accumulated, the subsequent separation step is carried out.
[0068] In the separation step, a process for separating the resin film from the member may be performed, or the resin film and the member may be separated from each other by natural falling or natural collapse.
[0069] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. EXAMPLES
[0070] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0071] [Preparation of emulsions and microparticles] [Preparation Example 1] A solution containing 20 parts by mass of ethylene carbonate-containing acrylic monomer (monomer produced using carbon dioxide as a raw material) in which n is 2 in the above-mentioned formula (3), 0.2 parts by mass of acrylic acid, 1 part by mass of polyoxyethylene polycyclic phenyl ether sulfate salt (manufactured by Nippon Nyukazai Co., Ltd., product name "Newcol 707SF") as an emulsifier, and 130 parts by mass of purified water was stirred at 70°C and 170 rpm.
[0072] Next, 0.3 parts by mass of ammonium persulfate (APS) was added to the above solution as a polymerization initiator, and the mixture was polymerized for 10 minutes by emulsion polymerization while stirring at 70° C. and 160 rpm to prepare a (meth)acrylic acid ester polymer. This resulted in an emulsion in which the (meth)acrylic acid ester polymer was dispersed as a dispersoid in water as a dispersion medium.
[0073] In the obtained emulsion, the mass ratio of the ethylene carbonate-containing acrylic monomer constituting the (meth)acrylic acid ester polymer (A) to acrylic acid was about 99:1, and the molar ratio was about 37:1. The solid content concentration of the above emulsion was calculated to be 14.4 mass%. Furthermore, when the particle size distribution of the dispersoid ((meth)acrylic acid ester polymer) in the emulsion was measured by DLS, the particle size (D50) was 142 nm.
[0074] The emulsion obtained as described above was left to stand overnight in an environment of 50°C to dry the dispersion medium. The residue remaining after drying was pulverized in a mortar to obtain fine particles. The fine particles were vapor-deposited with osmium and then observed with a scanning electron microscope (SEM). Circle detection and binarization of the obtained image revealed that the average particle size was 132 nm.
[0075] Furthermore, the amount (mass ratio) of carbon dioxide used (fixed) in the emulsion was calculated as the amount of CO2 fixed from the blending amount of the ethylene carbonate-containing acrylic monomer in the obtained emulsion, and was found to be 27.6%. This calculation was performed by dividing the molecular weight of CO2 (=44) by the molecular weight of the ethylene carbonate-containing acrylic monomer (A) (=158) and expressing the result as a percentage.
[0076] [Resin composition] Example 1-1 100 parts by mass (solid content equivalent, the same applies below) of the emulsion produced in Preparation Example 1 and 5 parts by mass of tetrabutylammonium bromide (TBAB) as a catalyst were mixed and left to stand overnight in an environment of 50° C. to dry the dispersion medium. A residue (resin composition) remaining after drying was obtained.
[0077] [Examples 1-2 to 1-8] Resin compositions were obtained in the same manner as in Example 1-1, except that the type and content of the catalyst were changed as shown in Table 1. In Table 2, "TBAB" means the above-mentioned tetrabutylammonium bromide, and "TBAF" means tetrabutylammonium fluoride.
[0078] Comparative Example 1-1 A resin composition was obtained in the same manner as in Example 1-1, except that no catalyst was used.
[0079] [Test Example 1-1] (Measurement of 5% weight loss temperature) The 5% weight loss temperature of the resin compositions prepared in Examples 1-1 to 1-8 was measured using a simultaneous differential thermal / thermogravimetric analyzer (manufactured by Shimadzu Corporation, product name "DTG-60") in accordance with JIS K7120: 1987. The results are shown in Table 1.
[0080] [Table 1]
[0081] As can be seen from each of Examples 1-1 to 1-4 and Examples 1-5 to 1-8 in Table 1, the 5% weight loss temperature was basically lower as the amount of catalyst was larger. This is presumably because the larger the amount of catalyst, the more efficiently the decomposition of the ethylene carbonate structure derived from the ethylene carbonate-containing acrylic monomer proceeded, and carbon dioxide was released more efficiently.
[0082] Furthermore, a comparison of Examples 1-1 to 1-4 with Examples 1-5 to 1-8 revealed that the 5% weight loss temperature was lower when tetrabutylammonium fluoride (TBAF) was used as a catalyst than when tetrabutylammonium bromide (TBAB) was used, that is, the decomposition of the ethylene carbonate structure proceeded more efficiently.
[0083] [Adhesive sheet] Example 2-1 95 parts by mass of n-butyl acrylate and 5 parts by mass of acrylic acid were copolymerized by emulsion polymerization to obtain a (meth)acrylic acid ester copolymer as the main material of the adhesive component. 100 parts by mass of the main material (36% by mass in terms of solid content, same below) was mixed with 10 parts by mass of the emulsion produced in Preparation Example 1 and 2 parts by mass of tetrabutylammonium bromide (TBAB) as a catalyst to obtain a coating solution of a resin composition (adhesive composition) with a solid content concentration of 33% by mass.
[0084] The obtained coating solution was applied by a coater to the release-treated surface of a heavy release type release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") in which one side of a polyethylene terephthalate film was treated for release with a silicone-based release agent. The coating layer was then heated at 100°C for 2 minutes to form a coating layer. Next, the coating layer on the heavy release type release sheet obtained above and a light release type release sheet (manufactured by Lintec Corporation, product name "SP-PET381031") in which one side of a polyethylene terephthalate film was treated for release with a silicone-based release agent were bonded together so that the release-treated surface of the light release type release sheet was in contact with the coating layer, to produce an adhesive sheet having a thickness of 25 μm, that is, an adhesive sheet 1 having a configuration of heavy release type release sheet / adhesive layer (thickness: 25 μm) / light release type release sheet. In addition, the coating layer on the heavy release type release sheet obtained above was bonded to a composite substrate (Alpet thickness: 40 μm) made by bonding aluminum foil and polyethylene terephthalate film together so that the release-treated surface of the light release type release sheet was in contact with the coating layer, thereby producing adhesive sheet 2.
[0085] [Examples 2-2 and 2-3] An adhesive sheet was obtained in the same manner as in Example 2-1, except that the content of the emulsion produced in Preparation Example 1 and the type and content of the catalyst were changed as shown in Table 2. In Table 2, "TBAB" means the above-mentioned tetrabutylammonium bromide, and "TBAF" means tetrabutylammonium fluoride.
[0086] Comparative Example 2-1 An adhesive sheet was obtained in the same manner as in Example 2-1, except that no catalyst was used.
[0087] [Test Example 2-1] (Measurement of 5% weight loss temperature) The 5% weight loss temperature of the adhesives constituting the adhesive layers prepared in Examples 2-1 to 2-3 and Comparative Example 2-1 was measured using a simultaneous differential thermal / thermogravimetric analyzer (manufactured by Shimadzu Corporation, product name "DTG-60") in accordance with JIS K7120: 1987. The results are shown in Table 2.
[0088] [Test Example 2-2] (Evaluation of foaming properties) The release sheet was peeled off from the pressure-sensitive adhesive sheets produced in Examples 2-1 to 2-3 and Comparative Example 2-1, and the exposed surface of the pressure-sensitive adhesive layer was attached to a glass plate to prepare a bubble checking sample. The bubble checking sample was heated by placing it in a thermostatic chamber at 180° C. for 1 minute, and the presence or absence of bubbles at the interface between the pressure-sensitive adhesive layer and the glass plate was confirmed before and after the heating. The foaming property was then evaluated based on the following criteria. The results are shown in Table 2. ⊚: Air bubbles were observed all over the interface. ◯: Air bubbles were partially observed at the interface. ×: Almost no air bubbles were observed at the interface.
[0089] [Test Example 2-3] (Evaluation of ease of dismantling) The release sheets were peeled off from the pressure-sensitive adhesive sheets produced in Examples 2-1 to 2-3 and Comparative Example 2-1, and the exposed surface of the pressure-sensitive adhesive layer was attached to a glass plate to prepare a sample for confirming dismantling property. The sample for confirming dismantling property was placed on a hot plate at 200° C. and heated for 2 minutes. During the heating, an attempt was made to manually peel off the interface between the pressure-sensitive adhesive layer and the glass plate. Then, the dismantling property was evaluated based on the following criteria. The results are shown in Table 2. ⊚: The film could be easily peeled off by hand. A: It was relatively easy to peel off by hand. ×: It was difficult to peel off by hand.
[0090] FIG. 1 shows the state of foaming after heating (FIG. 1a) and the state of peeling (FIG. 1b) for the dismantling confirmation sample of Example 2-2.
[0091] [Table 2]
[0092] As shown in Table 2, in the pressure-sensitive adhesive sheets of Examples 2-1 to 2-3, the 5% weight loss temperature of the pressure-sensitive adhesive layer was lower than that of the Reference Example. The lower the 5% weight loss temperature, the better the evaluation result of foamability (i.e., more bubbles were generated).
[0093] The above results are presumably due to the thermal decomposition of the ethylene carbonate structure in the (meth)acrylic acid ester polymer in the pressure-sensitive adhesive layers of Examples 2-1 to 2-3. That is, in Examples 2-1 to 2-3, the decomposition of the ethylene carbonate structure causes carbon dioxide to be released from the pressure-sensitive adhesive layer, which accelerates the weight loss and generates a large number of bubbles. [Industrial Applicability]
[0094] The resin composition of the present invention can be suitably used for the production of products that require easy dismantling. Specifically, the resin composition is useful in a wide range of fields, such as paints, adhesives, pressure sensitive adhesives, paper processing, dyes, fiber processing, printing inks, cement admixtures, coating agents, and films.
Claims
1. As a monomer unit constituting the polymer, 【Chemistry 1】 or fine particles containing the (meth)acrylic acid ester polymer as a dispersoid, a catalyst capable of performing a nucleophilic attack on a carbon atom constituting a carbonyl group in the ethylene carbonate structure, thereby decomposing the ethylene carbonate structure and releasing carbon dioxide; A resin composition comprising:
2. The particle diameter (D50) of the dispersoid is 10 nm or more and 1 μm or less, The average particle size of the fine particles is 10 nm or more and 1 μm or less. The resin composition according to claim 1 .
3. The resin composition according to claim 1, characterized in that the (meth)acrylic acid ester polymer contains the ethylene carbonate-containing monomer in an amount of 10 mass % or more and 99.9 mass % or less as a monomer unit constituting the polymer.
4. The resin composition according to claim 1, wherein the ethylene carbonate-containing acrylic monomer is a compound represented by the following formula (2) or the following formula (3): 【Chemistry 2】 (In the formula, n represents an integer of 0 or more.) 【Chemistry 3】 (In the formula, n represents an integer of 0 or more.)
5. the catalyst is a nucleophilic anion generator capable of generating a nucleophilic anion, The nucleophilic anion is a fluoride ion (F - ), chloride ion (Cl - ), bromide ion (Br - ), iodide ion (I - ) and hydroxide ion (OH - ) at least one of The resin composition according to claim 1 .
6. 2. The resin composition according to claim 1, wherein the catalyst is at least one of tetrabutylammonium bromide and tetra-N-butylammonium fluoride.
7. 2. The resin composition according to claim 1, wherein the (meth)acrylic acid ester polymer contains acrylic acid as a monomer unit constituting the polymer.
8. 2. The resin composition according to claim 1, wherein the (meth)acrylic acid ester polymer is obtained by emulsion polymerization of monomer units containing the ethylene carbonate-containing acrylic monomer.
9. The resin composition according to claim 1, characterized in that the fine particles are obtained by emulsion polymerization of monomer units containing the ethylene carbonate-containing acrylic monomer to produce an emulsion containing the (meth)acrylic acid ester polymer as a dispersoid, and then removing a dispersion medium constituting the emulsion to obtain a residue, and pulverizing the residue.
10. A resin film formed from the resin composition according to any one of claims 1 to 9.
11. An article comprising the resin film according to claim 10 and a member provided on at least one surface of the resin film.
12. A method for separating the resin film and the member in the article according to claim 11, comprising the steps of: heating the resin film to decompose the ethylene carbonate structure and generate carbon dioxide gas; A step of separating the resin film from the member by the carbon dioxide gas accumulated at the interface between the resin film and the member. A method for separating a material comprising the steps of:
Citation Information
Patent Citations
Adhesive composition, adhesive, laminate, and application of the same
JP2023035332A
JP214208A